The Assyrian Dictionary of the Oriental Institute of the University of Chicago. Editorial Board: Ignace J. Gelb, Benno Landsberger, A. Leo Oppenheim, Erica Reiner. Vol. 1 (A Part I). A. Leo Oppenheim, Editor-in-Charge, Erica Reiner, Editor, with the assistance of A. Kirk Grayson, Hans E. Hirsch, and Erle V. Leichty. Assistant to the Editors: Jane M. Rosenthal. Introduction by I. J. Gelb (1964)
a-alzibadar.